Pengaruh Media Busybook terhadap Kemampuan Mengenal Huruf pada Anak Kelompok B di TK Aster Kelurahan Molosipat W Kecamatan Kota Barat Kota Gorontalo - Mutia Mutia; Yakob Napu; Sri Wahyuningsi Laiya (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The Influence of Busybook Media on Letter Recognition Ability in Group B Children at Aster Kindergarten, Molosipat W Village, Kota Barat District, Gorontalo City. Early Childhood Education Teacher Education. Principal Supervisor I: Drs. Yakob Napu, M.Pd; Co-Supervisor II: Sri Wahyuningsi Laiya, S.Pd, M.Pd. This study aims to determine the effect of Busybook media on the letter recognition ability of Group B children at Aster Kindergarten, Molosipat W Village, West City District, Gorontalo City. This research used a quantitative approach with an experimental one-group pretest-posttest design. The sampling technique applied was purposive sampling, and data collection methods include tests and observation, where children’s letter recognition abilities were measured before and after the treatment using Busybook media. The instrument used in this study to assess letter recognition ability based on three indicators. The subjects of this study were children aged 5-6 years, with a sample size of 15 children. Data analysis results indicated a significant increase in children's letter recognition ability after the implementation of Busybook media. The t-test yielded a significance value of 0.000 with α = 0.05; since the significance value from the t-test is smaller than α (0.000 < 0.05), the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. It can be concluded that Busybook media has an effect on children's letter recognition ability and can be considered an effective teaching method in early childhood education. Keywords: Busybook Media, Letter Recognition Ability